Tariff-Mediated Network Effects versus Strategic Discounting: Evidence from German Mobile Telecommunications - Leon Zucchini; Jörg Claussen; Moritz Trüg (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2013)
Mobile telecommunication operators routinely charge subscribers lower prices for calls on their own network than for calls to other networks (on-net discounts). Studies on tariff-mediated network effects suggest this is due to large operators using on-net discounts to damage smaller rivals. Alternatively, research on strategic discounting suggests small operators use on-net discounts to advertise with low on-net prices. We test the relative strength of these effects using data on tariff setting in German mobile telecommunications between 2001 and 2009. We find that large operators are more likely to offer tariffs with on-net discounts but there is no consistently significant difference in the magnitude of discounts. Our results suggest that tariff-mediated network effects are the main cause of on-net discounts.
urn:nbn:de:bvb:19-epub-14848-4
Keywords: 650